Kinder im Gespräch - mit Kindern im Gespräch - Bose, Ines; Hannken-Illjes, Kati; Kurtenbach, Stephanie (Schriften zur Sprechwissenschaft und Phonetik, 2019)
How do children behave in conversations? The authors of this book provide answers that are relevant to research and practice. The analysis is based on authentic conversations in everyday situations. The discussion process and the situational embedding of the discussion actions are the focus of the investigations. The volume contains articles on argumentative conversations between children of preschool and elementary school age and on communication-promoting strategies of early childhood education professionals in daycare. In addition, framework conditions and observation instruments for communicative skills of kindergarten children are discussed and the use of digital media is also considered. Ines Bose, Prof. Dr., teaches and researches at the Institute for Music, Media and Speech Studies at Martin Luther University Halle-Wittenberg. Kati Hannken-Illjes, Prof. Dr., teaches and researches at the Institute for German Linguistics, Speech Science Group, at the Philipps University of Marburg. Stephanie Kurtenbach, Dr. phil., teaches and researches at the Institute for Music, Media and Speech Studies at the Martin Luther University Halle-Wittenberg.